Influence of digital literacy skills on job performance of library personnels in selected academic libraries in Southwestern, Nigeria (2020)
The study investigated influence of digital literacy skills on job performance of library personnel in selected academic libraries in Southwestern, Nigeria. Survey research method of expost-facto type was adopted for the study. The study population consisted of one hundred and four (104) library personnel’s in the two selected academic libraries (University of Ibadan and Obafemi Awolowo University). The population of the study consisted of para- professionals, professional librarians and library officers. Data were collected using questionnaire and were analysed using simple percentages, mean and Pearson’s Products Moment Correlation methods. The results revealed that library personnel in the two selected academic libraries possessed digital literacy skills such that they work easily with the computer without supervision (85.6%), use the computer every day at work (84.6%) and are skilled in using the computer (82.7%) among others. However, the digital literacy skills possessed by the librarians do not translate to job performance. Findings revealed a negative digital literacy skills on job performance of library personnel in the two universities (Df= 102, N= 104, r = -.060, P > 0.05). The study recommended that the University management should support the library and ensure the improvement of the library so as to continually meeting the needs of the library users, by procuring good computers to facilitate a digital library in order to facilitate resource sharing in the library to enhance teaching, learning and research.